Manufacturing method of printed wiring board

By immersing the insulating layer surface in an aqueous liquid and then treating it with an oxidizing agent solution in the presence of specific gases, the method addresses the issue of uneven roughening in printed wiring boards, enhancing the insulating layer's wiring formation ability.

JP2025048755APending Publication Date: 2025-04-03AJINOMOTO CO INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024143185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-20
Filing Date
2024-08-23
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

The surface of insulating layers in printed wiring boards is not uniformly roughened when treated with an oxidizing agent solution, leading to uneven roughening and poor wiring formation ability.

Method used

The method involves immersing the surface of the insulating layer in a specific aqueous liquid before roughening treatment with an oxidizing agent solution, and then contacting it with gases such as air or nitrogen to enhance uniformity.

Benefits of technology

This approach effectively suppresses uneven roughening, improving the wiring formation ability of the insulating layer and ensuring more consistent manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048755000001
    Figure 2025048755000001
  • Figure 2025048755000002
    Figure 2025048755000002
  • Figure 2025048755000003
    Figure 2025048755000003
Patent Text Reader

Abstract

To provide a manufacturing method of a printed wiring board that can suppress uneven roughening that occurs when an insulating layer surface is roughened with an oxidizing solution.SOLUTION: A manufacturing method of a printed wiring board includes the steps of (E) immersing the surface of an insulating layer in an aqueous liquid, and then contacting the surface of the insulating layer with one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas, and (F) roughening the surface of the insulating layer with an oxidizing agent solution, in this order, and the aqueous liquid used in the step (E) is either (1) or (2) below: (1) an oxidizing agent solution; (2) an aqueous liquid (excluding a swelling liquid) whose temperature difference with the oxidizing agent solution used in the step (F) is 20°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a printed wiring board. [Background technology]

[0002] Printed wiring boards are widely used in various electronic devices. In order to miniaturize and improve the functionality of electronic devices, finer and denser circuit wiring is required for printed wiring boards. Here, as a method for manufacturing printed wiring boards, a build-up method is known in which insulating layers and conductor layers are alternately stacked on an inner layer substrate. The insulating layer is formed, for example, by forming a resin composition layer containing a resin composition on the inner layer substrate and thermally curing the resin composition layer on the inner layer substrate.

[0003] In a method for manufacturing a printed wiring board, as disclosed in Patent Document 1, for example, a desmear treatment may be performed on an insulating layer formed for the purpose of removing resin residue (smear) in a via hole formed in the insulating layer or roughening the surface of the insulating layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-163825 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the surface of the insulating layer is roughened (or desmeared) with an oxidizing agent solution, the surface of the insulating layer is not uniformly roughened, and uneven roughening may occur. Such uneven roughening of the insulating layer surface may deteriorate the wiring formability of the insulating layer.

[0006] An object of the present invention is to provide a method for producing a printed wiring board, which can suppress uneven roughening that occurs when the surface of an insulating layer is roughened with an oxidizing agent solution. [Means for solving the problem]

[0007] As a result of intensive research into the above-mentioned problems, the inventors discovered that the above-mentioned problems can be solved by including a step of immersing the surface of the insulating layer in a specific aqueous liquid and then contacting it with a specific gas before the roughening treatment in a method for manufacturing a printed wiring board, and thus completed the present invention.

[0008] That is, the present invention includes the following. <1> (E) a step of immersing the surface of the insulating layer in an aqueous liquid and then contacting the surface of the insulating layer with one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas; and (F) a step of roughening the surface of the insulating layer with an oxidizing agent solution, in this order; A method for producing a printed wiring board, wherein the aqueous liquid used in step (E) is the following (1) or (2): (1) Oxidizing agent solution (2) An aqueous liquid (excluding the swelling liquid) whose temperature difference with the oxidizing agent solution used in step (F) is 20°C or less. <2> The gas used in step (E) is air; <1> A method for producing a printed wiring board according to claim 1. <3> In step (E), the time for contacting the surface of the insulating layer with the gas is 5 seconds or more and 120 seconds or less. <1> or <2> A method for producing a printed wiring board according to claim 1. <4> In step (E), the time for contacting the surface of the insulating layer with the gas is 10 seconds or more and 60 seconds or less. <3> A method for producing a printed wiring board according to claim 1. <5> In step (E), the time for immersing the surface of the insulating layer in the aqueous liquid is t E In step (F), the time for treating the surface of the insulating layer with the oxidizing agent solution is t F When t E and t F but, 0.02≦tE / (t E +t F )≦0.25 The following relation is satisfied: <1> ~ <4> 2. A method for producing a printed wiring board according to claim 1 . <6> The aqueous liquid used in step (E) is pure water; <1> ~ <5> 2. A method for producing a printed wiring board according to claim 1 . <7> Before step (E), a step (C) of drilling holes in the insulating layer is included; <1> ~ <6> 2. A method for producing a printed wiring board according to claim 1 . <8> After the step (F), a step (H) of forming a conductor layer on the insulating layer is included. <1> ~ <7> 2. A method for producing a printed wiring board according to claim 1 . <9> Before step (E), (A) forming a resin composition layer containing a resin composition on an inner layer substrate; and (B) curing the resin composition layer to form an insulating layer, <1> ~ <8> 2. A method for producing a printed wiring board according to claim 1 . <10> The resin composition contained in the resin composition layer contains (a) an epoxy resin and (b) an active ester-based curing agent; <9> A method for producing a printed wiring board according to claim 1. <11> (a) when the number of epoxy groups in the epoxy resin is taken as 1, (b) the number of active ester groups in the active ester curing agent is 0.3 or more and 2.0 or less; <10> A method for producing a printed wiring board according to claim 1. Effect of the Invention

[0009] According to the present invention, it is possible to provide a method for producing a printed wiring board that can suppress uneven roughening that occurs when the surface of an insulating layer is roughened with an oxidizing agent solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0011] [Resin composition] Before describing each step in detail, the resin composition contained in the resin composition layer formed on the inner layer substrate in step (A) in the method for producing a printed wiring board of the present invention will be described. Hereinafter, the resin composition contained in the resin composition layer formed on the inner layer substrate may be simply referred to as the "resin composition".

[0012] In one embodiment, the resin composition includes (a) an epoxy resin and (b) an active ester-based curing agent. The resin composition may further include (c) an inorganic filler, (d) other curing agents, (e) a thermoplastic resin, (f) a curing accelerator, (g) other additives, and (h) a solvent, as necessary. Each component included in the resin composition will be described in detail below.

[0013] <(a) Epoxy resin> The resin composition contains an epoxy resin (a) as component (a). By including the epoxy resin (a) in the resin composition, a cured product exhibiting good mechanical strength and insulation reliability can be obtained. The epoxy resin (a) may be used alone or in combination of two or more kinds.

[0014] (a) Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, and glycidyl ester type Examples of the epoxy resin include epoxy resins, glycidyl cyclohexane type epoxy resins, alkyl diglycidyl ether type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, phenolphthalimidine type epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more.

[0015] The resin composition preferably contains, as component (a), an epoxy resin having two or more epoxy groups in one molecule. From the viewpoint of significantly obtaining the desired effects of the present invention, the ratio of the epoxy resin having two or more epoxy groups in one molecule to 100% by mass of the epoxy resin (a) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, and is usually 100% by mass or less.

[0016] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only a liquid epoxy resin as component (a), may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin. Of these, from the viewpoint of achieving the effects of the present invention significantly, it is preferable to contain a combination of a liquid epoxy resin and a solid epoxy resin.

[0017] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0018] Preferred liquid epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, glycidyl amine type epoxy resins, and epoxy resins having a butadiene structure, glycidyl cyclohexane type epoxy resins, phenolphthalimidine type epoxy resins, and alkyl diglycidyl ether type epoxy resins, and more preferred are glycidyl cyclohexane type epoxy resins.

[0019] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; and "ZX1" manufactured by Nippon Steel Chemical & Material Co., Ltd. Examples of epoxy resins include "EX-721" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nagase ChemteX Corporation, "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation, "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation, "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Corporation, and "YED216D" (alkyl diglycidyl ether type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.

[0020] As the solid epoxy resin, a solid epoxy resin having two or more epoxy groups in one molecule is preferable, a solid epoxy resin having three or more epoxy groups in one molecule is more preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is even more preferable.

[0021] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin are preferred, and bixylenol type epoxy resin, biphenyl type epoxy resin, and naphthylene ether type epoxy resin are more preferred.

[0022] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000", "NC3000L" manufactured by Nippon Kayaku Co., Ltd. Examples of epoxy resins include "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL6121" (biphenyl type epoxy resin), "YX4000H", "YX4000HK" (bixylenol type epoxy resin), and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), and "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; and "WHR-991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more.

[0023] When a liquid epoxy resin and a solid epoxy resin are used in combination as component (a), the ratio by mass (liquid epoxy resin:solid epoxy resin) is preferably 1:0.01 to 1:50, more preferably 1:0.05 to 1:20, and even more preferably 1:0.1 to 1:10.

[0024] The epoxy equivalent of the (a) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 50 g / eq. to 3,000 g / eq., even more preferably 80 g / eq. to 2,000 g / eq., and even more preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of an epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0025] The weight average molecular weight (Mw) of the (a) epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and further preferably 400 to 1,500. The weight average molecular weight (Mw) of the (a) epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0026] The content of the (a) epoxy resin in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 5 mass% or more, more preferably 8 mass% or more, and even more preferably 10 mass% or more, and the upper limit is preferably 40 mass% or less, more preferably 30 mass% or less, and even more preferably 25 mass% or less.

[0027] In this specification, the term "non-volatile components" refers to all non-volatile components contained in the resin composition excluding the (h) solvent, which will be described later.

[0028] The content of the (a) epoxy resin in the resin composition is not particularly limited, but when the resin component in the resin composition is 100% by mass, it is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, and the upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less.

[0029] In this specification, the term "resin component" refers to components contained in a resin composition excluding the (c) inorganic filler described below.

[0030] <(b) Active ester curing agent> The resin composition contains an active ester curing agent (b) as the component (b). The active ester curing agent (b) as the component (b) does not include those corresponding to the above-mentioned component (a). The active ester curing agent (b) may be used alone or in combination of two or more kinds.

[0031] (b) As the active ester curing agent, generally, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, the active ester curing agent is preferably an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound, and more preferably an active ester curing agent obtained from a carboxylic acid compound and an aromatic hydroxy compound. As the carboxylic acid compound, either an aromatic carboxylic acid compound or an aliphatic carboxylic acid compound may be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof. Examples of aromatic hydroxy compounds include (i) polyaddition products of unsaturated aliphatic cyclic compounds containing two double bonds in one molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to the carbon atoms on the aromatic ring, and (iv) aromatic monools having one hydroxyl group bonded to the carbon atoms on the aromatic ring. Examples of polyaddition products of unsaturated aliphatic cyclic compounds and phenols include polyaddition products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene with phenols that may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, etc.), and specifically, for example, dicyclopentadiene-phenols polyaddition products. Examples of bisphenol compounds include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M.Examples of aromatic polyols having two or more hydroxyl groups bonded to a carbon atom on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, benzenetriol, phenol novolak, etc. Examples of aromatic monools having one hydroxyl group bonded to a carbon atom on an aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halophenol, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, halonaphthol, etc.

[0032] Specifically, (b) active ester curing agent includes dicyclopentadiene type active ester curing agent, naphthalene type active ester curing agent containing naphthalene structure, active ester curing agent containing acetylated phenol novolac, active ester curing agent containing benzoylated phenol novolac, active ester curing agent which is acetylated phenol novolac, active ester curing agent containing styryl group and naphthalene structure, etc., and dicyclopentadiene type active ester curing agent is preferable. As dicyclopentadiene type active ester curing agent, active ester curing agent containing dicyclopentadiene type diphenol structure is preferable. "Dicyclopentadiene type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.

[0033] (b) Commercially available products of active ester curing agents include active ester resins containing a dicyclopentadiene-type diphenol structure, such as "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "HPC-8000L-65TM" (manufactured by DIC Corporation); and active ester resins containing a naphthalene structure, such as "EXB-8100L-65T", "EXB-8150-60T", "EXB-8150-62T", "EXB-9416-70BK", "HPC-8150-60T", and "HPC-8150-62T". ", "HP-B-8151-62T", and "HP-C-8151-62T" (manufactured by DIC Corporation); a phosphorus-containing active ester resin such as "EXB9401" (manufactured by DIC Corporation); an active ester resin which is an acetylated product of phenol novolac such as "DC808" (manufactured by Mitsubishi Chemical Corporation); active ester resins which are benzoylated products of phenol novolac such as "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation); and an active ester resin containing a styryl group and a naphthalene structure such as "PC1300-02-65MA" (manufactured by Air Water Corporation).

[0034] (b) The active ester group equivalent of the active ester curing agent is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and further preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of the active ester curing agent containing one equivalent of an active ester group.

[0035] When the number of epoxy groups in (a) epoxy resin is 1, the number of active ester groups in (b) active ester curing agent is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.3 or more, and preferably 3.0 or less, more preferably 2.0 or less, even more preferably 1.5 or less. Here, "the number of epoxy groups in epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. In addition, "the number of active ester groups in active ester curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the active ester curing agent present in the resin composition by the active ester group equivalent.

[0036] The content of the (b) active ester-based curing agent in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100 mass%, it is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more, and the upper limit is preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 35 mass% or less.

[0037] The content of the (b) active ester-based curing agent in the resin composition is not particularly limited, but when the resin component in the resin composition is taken as 100 mass%, it is preferably 20 mass% or more, more preferably 30 mass% or more, and even more preferably 35 mass% or more, and the upper limit is preferably 80 mass% or less, more preferably 75 mass% or less, and even more preferably 70 mass% or less.

[0038] The mass ratio of the (b) active ester-based curing agent to the (a) epoxy resin (mass of component (b) / mass of component (a)) is not particularly limited, but is preferably 0.50 or more, more preferably 0.60 or more, and even more preferably 0.65 or more, and the upper limit is preferably 4.0 or less, more preferably 3.0 or less, and even more preferably 2.7 or less.

[0039] <(c) Inorganic filler> The resin composition may contain an inorganic filler (c) as an optional component. The inorganic filler (c) as the component (c) may be contained in the resin composition in the form of particles. The inorganic filler (c) may be used alone or in combination of two or more kinds.

[0040] (c) Examples of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as the silica. These may be used alone or in combination of two or more.

[0041] (c) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "Cellspheres" and "MGH-005" manufactured by Taiheiyo Cement Corporation.

[0042] (c) The average particle size of the inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, 2 μm or less, 1 μm or less, or 0.7 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.07 μm or more, 0.1 μm or more, or 0.2 μm or more. The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the particle size at which the cumulative distribution value is 50% (median diameter, 50% particle size D 50 ) can be measured as the average particle size. The measurement sample can be prepared by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing them by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths and a flow cell method to measure the volumetric particle size distribution of the inorganic filler, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0043] (c) The specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or more or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 / g or less. (c) The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0044] The (c) inorganic filler is preferably surface-treated with a suitable surface treatment agent. By being surface-treated, the moisture resistance and dispersibility of the (c) component can be improved. Examples of the surface treatment agent include silane coupling agents such as vinyl silane coupling agents, epoxy silane coupling agents, styryl silane coupling agents, (meth)acrylic silane coupling agents, amino silane coupling agents, isocyanurate silane coupling agents, ureido silane coupling agents, mercapto silane coupling agents, isocyanate silane coupling agents, and acid anhydride silane coupling agents; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; and silazane compounds. The surface treatment agent may be used alone or in combination of two or more.

[0045] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0046] From the viewpoint of improving dispersibility, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100 mass% of (c) inorganic filler is preferably surface-treated with 0.2 to 8 mass% of the surface treatment agent, more preferably with 0.2 to 5 mass% of the surface treatment agent, and even more preferably with 0.3 to 3 mass% of the surface treatment agent.

[0047] The degree of surface treatment with a surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. (c) The amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m from the viewpoint of improving the dispersibility of the inorganic filler. 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, the carbon amount per unit surface area of ​​the (c) inorganic filler is preferably 1.0 mg / m from the viewpoint of preventing an increase in the melt viscosity of the resin composition. 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is more preferable. The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, an "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0048] The content of the (c) inorganic filler in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100% by mass, it may be, for example, 0% by mass or more, 1% by mass or more, or 5% by mass or more, preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more. The upper limit of the content may be, for example, 90% by mass or less, preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 68% by mass or less, 67% by mass or less, or 66% by mass or less.

[0049] <(d) Other hardeners> The resin composition may contain, as an optional component, (d) other curing agents other than (b) active ester curing agents. In this specification, (d) other curing agents are curing agents other than those corresponding to (b) active ester curing agents explained above. As the (d) component, (d) other curing agents may be used alone or in combination of two or more types.

[0050] (d) Other curing agents are not particularly limited, but examples thereof include phenol-based curing agents, naphthol-based curing agents, carbodiimide-based curing agents, acid anhydride-based curing agents, amine-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, thiol-based curing agents, etc. Among them, (d) other curing agents preferably include one or more curing agents selected from phenol-based curing agents and naphthol-based curing agents.

[0051] As the phenol-based curing agent and naphthol-based curing agent, those having a novolac structure are preferred from the viewpoint of heat resistance and water resistance. Also, from the viewpoint of adhesion to the conductor layer, nitrogen-containing phenol-based curing agents and nitrogen-containing naphthol-based curing agents are preferred, and triazine skeleton-containing phenol-based curing agents and triazine skeleton-containing naphthol-based curing agents are more preferred. From the viewpoint of realizing an insulating layer having good heat resistance, water resistance, and adhesion to the conductor layer, phenol-based curing agents and naphthol-based curing agents having both a triazine skeleton and a novolac structure are particularly suitable. Specific examples of phenol-based curing agents and naphthol-based curing agents include, for example, "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemical Industry Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; and "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-37" manufactured by Nippon Steel Chemical & Material Co., Ltd. 5" and "SN-395" manufactured by DIC Corporation; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by Gun-ei Chemical Co., Ltd.; and the like.

[0052] The carbodiimide curing agent is a compound having one or more carbodiimide groups (-N=C=N-) in one molecule, and the carbodiimide curing agent is preferably a compound having two or more carbodiimide groups in one molecule. Specific examples of the carbodiimide curing agent include Carbodilite (registered trademark) V-03 (carbodiimide group equivalent: 216 g / eq., V-05 (carbodiimide group equivalent: 262 g / eq.), V-07 (carbodiimide group equivalent: 200 g / eq.), V-09 (carbodiimide group equivalent: 200 g / eq.), and Stavaxol (registered trademark) P (carbodiimide group equivalent: 302 g / eq.) manufactured by Lanxess.

[0053] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Resonaq, and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Chemical Industries, Ltd.

[0054] The amine-based curing agent may be a curing agent having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propanediamine, and the like. bis(4-aminophenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. The amine-based curing agent may be a commercially available product, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0055] Specific examples of benzoxazine-based curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0056] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include arxada's "PT30" and "PT60" (phenol novolac type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been triazine-converted into a trimer).

[0057] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0058] When the number of epoxy groups in (a) epoxy resin is taken as 1, the number of active groups in (d) other curing agents is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.08 or more, and preferably 2.0 or less, more preferably 1.0 or less, even more preferably 0.5 or less. Here, "the number of active groups in other curing agents" refers to the total value obtained by dividing the mass of the non-volatile components of curing agents other than the active ester curing agent present in the resin composition by the active group equivalent of the curing agent.

[0059] (a) When the number of epoxy groups in the epoxy resin is taken as 1, the number of active groups in the entire curing agent is preferably 0.01 or more, more preferably 0.1 or more, even more preferably 0.4 or more, and preferably 5.0 or less, more preferably 3.0 or less, even more preferably 2.0 or less. Here, the "number of active groups in the entire curing agent" is the total value of the number of active ester groups in the active ester curing agent and the number of active groups in the other curing agents.

[0060] The content of the (d) other curing agent in the resin composition is not particularly limited, but may be, for example, 0% by mass or more, 0.1% by mass or more, or 0.5% by mass or more, preferably 0.7% by mass or more, more preferably 0.9% by mass or more, and even more preferably 1% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. The upper limit of the content may be, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less.

[0061] The content of the (d) other curing agent in the resin composition is not particularly limited, but when the resin component in the resin composition is taken as 100 mass%, it may be, for example, 0 mass% or more, 0.5 mass% or more, or 1.0 mass% or more, preferably 2.0 mass% or more, more preferably 3.0 mass% or more, and even more preferably 3.5 mass% or more. The upper limit of the content may be, for example, 30 mass% or less, preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 8 mass% or less.

[0062] The mass ratio of the (d) other curing agent to the (a) epoxy resin (mass of component (d) / mass of component (a)) is not particularly limited, but can be, for example, 0.01 or more, preferably 0.05 or more, more preferably 0.10 or more, and even more preferably 0.13 or more, and the upper limit is preferably 1 or less, more preferably 0.5 or less, and even more preferably 0.2 or less.

[0063] The mass ratio of the (b) active ester-based curing agent and (d) other curing agent to the (a) epoxy resin ((mass of component (b)+mass of component (d)) / mass of component (a)) is preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 0.8 or more, and the upper limit thereof is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less.

[0064] <(e) Thermoplastic resin> The resin composition may contain (e) a thermoplastic resin as an optional component. The (e) thermoplastic resin as the (e) component does not include those corresponding to the above-mentioned (a) to (d). The (e) thermoplastic resin may be used alone or in combination of two or more kinds.

[0065] Examples of the (e) thermoplastic resin include a phenoxy resin, a polyimide resin, a polyvinyl acetal resin, a polyolefin resin, a polybutadiene resin, a polyamideimide resin, a polyetherimide resin, a polysulfone resin, a polyethersulfone resin, a polyphenylene ether resin, a polycarbonate resin, a polyetheretherketone resin, a polyester resin, etc. In one embodiment, the (e) thermoplastic resin preferably includes a phenoxy resin.

[0066] The polystyrene-equivalent weight average molecular weight of the thermoplastic resin is preferably 8000 or more, more preferably 10000 or more, even more preferably 20000 or more or 30000 or more. The upper limit is preferably 100000 or less, more preferably 70000 or less, even more preferably 60000 or less. The polystyrene-equivalent Mw of the thermoplastic resin is measured by a GPC method. Specifically, the polystyrene-equivalent Mw of the thermoplastic resin is measured at a column temperature of 40° C. using a measuring device LC-9A / RID-6A manufactured by Shimadzu Corporation, a column Shodex K-800P / K-804L / K-804L manufactured by Resonaq, and chloroform or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.

[0067] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YL7800BH40", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0068] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (disclosed in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (disclosed in JP-A-2002-12667 and JP-A-2000-319386, etc.).

[0069] Examples of polyvinyl acetal resins include polyvinyl formal resins and polyvinyl butyral resins, and polyvinyl butyral resins are preferred.Specific examples of polyvinyl acetal resins include S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0070] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0071] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0072] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0073] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0074] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0075] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC Corp. A specific example of the polyetherimide resin is ULTEM manufactured by GE Corp.

[0076] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include Mitsubishi Gas Chemical's "FPC0220," Asahi Kasei's "T6002" and "T6001" (polycarbonate diols), and Kuraray's "C-1090," "C-2090," and "C-3090" (polycarbonate diols). Specific examples of polyether ether ketone resins include Sumitomo Chemical's "Sumiploy K."

[0077] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0078] The content of the (e) thermoplastic resin in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100% by mass, it may be, for example, 0% by mass or more, 0.1% by mass or more, or 0.5% by mass or more, preferably 0.8% by mass or more, more preferably 1.0% by mass or more, and even more preferably 1.1% by mass or more. The upper limit of the content may be, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0079] The content of the (e) thermoplastic resin in the resin composition is not particularly limited, but when the resin component in the resin composition is taken as 100% by mass, it may be, for example, 0% by mass or more, 0.1% by mass or more, or 0.5% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. The upper limit of the content may be, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0080] <(f) Curing accelerator> The resin composition may contain a curing accelerator (f) as an optional component. The curing accelerator (f) as the component (f) does not include those corresponding to the above-mentioned components (a) to (e). By including the component (f), it becomes possible to further accelerate the curing of the component (a). The curing accelerator (f) may be used alone or in combination of two or more kinds.

[0081] (f) Examples of the curing accelerator include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and peroxide-based curing accelerators.

[0082] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0083] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.

[0084] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, and adducts of imidazole compounds and epoxy resins, with 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole being preferred. As the imidazole-based curing accelerator, commercially available products may be used, such as "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0085] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0086] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0087] Examples of peroxide-based curing accelerators include cyclohexanone peroxide, tert-butyl peroxybenzoate, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl cumyl peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, and tert-butyl hydroperoxide. Commercially available peroxide-based curing accelerators can be used, such as "Percumyl D" manufactured by NOF Corporation.

[0088] The content of the (f) curing accelerator in the resin composition is not particularly limited, but when the non-volatile components in the resin composition are taken as 100% by mass, it may be, for example, 0% by mass or more, 0.001% by mass or more, or 0.010% by mass or more, preferably 0.015% by mass or more, more preferably 0.020% by mass or more, and even more preferably 0.025% by mass or more. The upper limit of the content may be, for example, 5% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.06% by mass or less.

[0089] The content of the (f) curing accelerator in the resin composition is not particularly limited, but when the resin component in the resin composition is taken as 100% by mass, it may be, for example, 0% by mass or more, 0.001% by mass or more, or 0.01% by mass or more, preferably 0.03% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.06% by mass or more. The upper limit of the content may be, for example, 10% by mass or less, preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less.

[0090] <(g) Other additives> In addition to the above-mentioned components, the resin composition may further contain (g) other additives as optional components. Examples of (g) other additives include radical polymerizable compounds, elastomers, polymerization initiators, organometallic compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds, colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black, polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine, leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents, thickeners such as bentone and montmorillonite, defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers, ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers, adhesion improvers such as urea silane, adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters, hindered forms, and the like. antioxidants such as phenol-based antioxidants; fluorescent brightening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiation assistants such as tertiary amines; and photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, and thioxanthones. The (g) other additives as the component (g) may use one type alone, or two or more types may be used in combination.

[0091] <(h) Solvent> The resin composition may contain (h) a solvent as a volatile component in addition to the non-volatile components described above. As the (h) solvent, a known solvent may be appropriately used, and the type is not particularly limited, and it is preferable that the solvent is an organic solvent. As the (h) solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methyl methoxypropionate, etc. Examples of the solvent include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (h) The solvent may be used alone or in combination of two or more in any ratio.

[0092] The resin composition can be produced, for example, by adding and mixing the (a) component, the (b) component, and, if necessary, the (c), (d), (e), (f), (g), and (h) components in any preparation vessel in any order and / or all or part of them at the same time. In the process of adding and mixing each component, the temperature can be appropriately set, and heating and / or cooling may be performed temporarily or throughout. In the process of adding and mixing or thereafter, the resin composition may be stirred or shaken using a stirring device or shaking device such as a mixer to disperse the resin composition uniformly. Simultaneous with stirring or shaking, degassing may be performed under low pressure conditions such as under vacuum.

[0093] [Resin sheet] The above-mentioned resin composition may be used as it is, or may be used in the form of a sheet-like laminate material containing the resin composition. Examples of the sheet-like laminate material include the resin sheet described in detail below.

[0094] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support, and the resin composition layer includes the above-mentioned resin composition.

[0095] The thickness of the resin composition layer may vary depending on the application, and may be appropriately determined depending on the application. For example, the thickness of the resin composition layer is preferably 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less from the viewpoint of thinning the printed wiring board or semiconductor package. The lower limit of the thickness of the resin composition layer is not particularly limited, but may be, for example, 1 μm or more, 5 μm or more, etc.

[0096] Examples of the support include a thermoplastic resin film, a metal foil, and a release paper, and a thermoplastic resin film and a metal foil are preferred. Thus, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.

[0097] When a thermoplastic resin film is used as the support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0098] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0099] The support may be subjected to a matte treatment, a corona treatment, or an antistatic treatment on the surface to be bonded to the resin composition layer. In addition, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used as the support. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0100] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0101] When a metal foil is used as the support, a metal foil with a support substrate may be used, which is a thin metal foil with a peelable support substrate attached thereto. In one embodiment, the metal foil with a support substrate includes a support substrate, a release layer provided on the support substrate, and a metal foil provided on the release layer. When a metal foil with a support substrate is used as the support, the resin composition layer is provided on the metal foil.

[0102] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the release layer is not particularly limited as long as it can release the metal foil from the supporting substrate, and examples thereof include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, etc.

[0103] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.

[0104] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm, and the thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.

[0105] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and the like to the surface of the resin composition layer and scratches.

[0106] The resin sheet can be produced, for example, by preparing a resin varnish by dissolving the liquid resin composition in an organic solvent or by applying the resin varnish onto a support using a die coater or the like, and then drying the resin varnish to form a resin composition layer.

[0107] The organic solvent may be the same as the (h) solvent described as a component of the resin composition. The organic solvent may be used alone or in combination of two or more.

[0108] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of the organic solvent in the resin composition layer becomes 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition or resin varnish, for example, when a resin composition or resin varnish containing 30% by mass to 60% by mass of the organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0109] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, the resin sheet can be used by peeling off the protective film.

[0110] The above-mentioned resin sheet can be suitably used to form an insulating layer of a printed wiring board (for the insulating layer of a printed wiring board), and can be more suitably used to form an interlayer insulating layer of a printed wiring board (for the insulating edge layer of a printed wiring board). The resin sheet can also be suitably used to form an insulating layer of a rewiring board of a semiconductor package (for the insulating layer of a rewiring board). That is, the above-mentioned resin sheet can be suitably used as an insulating layer of a circuit board.

[0111] [Printed wiring board manufacturing method] In one embodiment, the printed wiring board includes an insulating layer formed of a cured product obtained by curing the above-mentioned resin composition.

[0112] The method for producing a printed wiring board of the present invention comprises the steps of: (E) a step of immersing the surface of the insulating layer in an aqueous liquid and then contacting the surface of the insulating layer with one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas; and (F) a step of roughening the surface of the insulating layer with an oxidizing agent solution, The aqueous liquid used in step (E) is characterized in that it is the following (1) or (2): (1) Oxidizing agent solution (2) An aqueous liquid (excluding the swelling liquid) whose temperature difference with the oxidizing agent solution used in step (F) is 20°C or less.

[0113] According to the method for producing a printed wiring board of the present invention, it is possible to suppress uneven roughening that occurs when the surface of an insulating layer is roughened with an oxidizing agent solution. According to the method for producing a printed wiring board of the present invention, specifically, the average number of spots per visual field on the surface of the insulating layer can be preferably less than 40, more preferably less than 30, even more preferably less than 25, and even more preferably less than 20. There is no particular limit to the lower limit of the average number of spots per visual field on the surface of the insulating layer, and it may be 0 or more than 0. The number of spots per visual field on the surface of the insulating layer can be measured according to the method described in the examples below.

[0114] In one embodiment of the method for producing a printed wiring board of the present invention, an insulating layer having a small arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment can be produced. The arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is preferably 300 nm or less, more preferably 250 nm or less, and even more preferably 200 nm or less. The lower limit is not particularly limited, but is preferably 30 nm or more, more preferably 40 nm or more, and even more preferably 50 nm or more. The arithmetic mean roughness (Ra) of the insulating layer surface can be measured using a non-contact surface roughness meter. The arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment can be measured using a non-contact surface roughness meter.

[0115] Hereinafter, in this specification, the case where the aqueous liquid used in step (E) is (1) an oxidant solution will be referred to as the "first embodiment," and the case where the aqueous liquid used in step (E) is (2) an aqueous liquid (excluding the swelling liquid) whose temperature difference with the oxidant solution used in step (F) is 20°C or less will be referred to as the "second embodiment."

[0116] The method for producing a printed wiring board of the present invention includes a step (E) prior to the step (F). The step (E) suppresses the occurrence of uneven roughening of the insulating layer. Without being bound by a particular theory, the present inventors speculate that the mechanism by which the above-mentioned effects are obtained is as follows. However, the technical scope of the present invention is not limited by the mechanism described below.

[0117] In the method for producing a printed wiring board, the oxidizing agent solution used in the roughening treatment may be heated to 60°C to 100°C before use. However, when an insulating layer at room temperature (15°C to 25°C) is immersed in a relatively high-temperature oxidizing agent solution, the gas dissolved in the high-temperature oxidizing agent solution may adhere to the surface of the insulating layer as minute bubbles that cannot be visually confirmed due to stimulation caused by the temperature difference. In addition, the method for producing a printed wiring board may include a step of immersing the insulating layer in a swelling liquid for swelling treatment and washing the swelling liquid with water before the roughening treatment with the oxidizing agent solution. However, the water used to wash the swelling liquid is used without heating, so that the temperature is relatively low compared to the oxidizing agent solution. When the insulating layer is immersed in the oxidizing agent solution after washing, the gas dissolved in the oxidizing agent solution may adhere to the surface of the insulating layer as minute bubbles that cannot be visually confirmed due to stimulation caused by the temperature difference or difference in liquid properties. According to the inventor's investigation, it is believed that minute uneven roughening of the insulating layer surface occurs because minute bubbles that cannot be seen with the naked eye attached to the insulating layer surface partially inhibit the roughening treatment using the oxidizing agent solution. Note that minute uneven roughening of the insulating layer surface, which is presumed to be caused by minute bubbles that cannot be seen with the naked eye attached to the insulating layer surface, is an issue that has become apparent with the advancement of fine wiring.

[0118] Therefore, in the manufacturing method according to the present embodiment, a step of immersing the insulating layer surface in an aqueous liquid and then contacting the insulating layer surface with one or more gases selected from the group consisting of air, rare gas, nitrogen gas, and carbon dioxide gas is added before the step of treating the insulating layer surface with an oxidizing agent solution. In the first embodiment, the insulating layer is immersed in the oxidizing agent solution once, taken out once, and then immersed in the oxidizing agent solution. In this embodiment, it is considered that the generation of minute bubbles that cannot be confirmed by visual inspection on the insulating layer surface is suppressed by immersing the insulating layer in an oxidizing agent solution in a state where chemical stimulation is low. In addition, in the second embodiment, the insulating layer is immersed in an aqueous liquid having a temperature difference from the oxidizing agent solution of 20° C. or less, taken out once, and then immersed in the oxidizing agent solution. In this embodiment, it is considered that the generation of minute bubbles that cannot be confirmed by visual inspection on the insulating layer surface is suppressed by suppressing stimulation caused by the temperature difference. Therefore, it is presumed that the manufacturing method according to the present embodiment can suppress the partial inhibition of the roughening treatment due to bubbles, and therefore the generation of minute roughening unevenness on the insulating layer surface can be suppressed.

[0119] In one embodiment, the method for producing a printed wiring board of the present invention further comprises the steps of: (A) forming a resin composition layer containing a resin composition on an inner layer substrate; and and (B) a step of curing the resin composition layer to form an insulating layer.

[0120] In one embodiment, the method for producing a printed wiring board of the present invention may include a step (C) of drilling holes in the insulating layer before step (E). When the method for producing a printed wiring board of the present invention includes steps (A) and (B), step (C) may be performed after step (B) and before (E).

[0121] In one embodiment, the method for producing a printed wiring board of the present invention may include a step (D) of swelling the surface of the insulating layer before step (E). When the method for producing a printed wiring board of the present invention includes steps (A) and (B), step (D) may be performed after step (B) and before (E). When the method for producing a printed wiring board of the present invention includes step (C), step (D) may be performed after step (C) and before (E).

[0122] In one embodiment, the method for producing a printed wiring board of the present invention may include, after step (F), a step (G) of neutralizing the surface of the insulating layer.

[0123] In one embodiment, the method for producing a printed wiring board of the present invention may include, after step (F), a step (H) of forming a conductor layer on the insulating layer. When the method for producing a printed wiring board of the present invention includes step (G), step (H) may be performed after step (G).

[0124] Hereinafter, each step in the method for producing a printed wiring board of the present invention will be described in order of steps.

[0125] <Process (A) and Process (B)> The method for producing a printed wiring board of the present invention may include, as optional steps, (A) a step of forming a resin composition layer containing a resin composition on an inner layer substrate, and (B) a step of curing the resin composition layer to form an insulating layer, in this order.

[0126] Examples of the "inner layer substrate" used in step (A) include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate." In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the above-mentioned "inner layer substrate." When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0127] In carrying out step (A), a resin composition layer containing a resin composition may be formed on the inner layer substrate by laminating the resin sheet so that the resin composition layer of the resin sheet is bonded to the inner layer substrate. As the resin sheet, the one described above in [Resin sheet] may be used.

[0128] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). The thermocompression bonding member may be pressed directly onto the resin sheet, or may be pressed via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.

[0129] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.

[0130] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0131] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0132] The support may be removed between step (A) and step (B), or after step (B). When the support is removed after step (B), the support may be removed between step (B) and step (E), or after step (F). When the method for producing a printed wiring board further includes step (H), the support is preferably removed before step (H). That is, when the method for producing a printed wiring board includes (H), the support is preferably removed between step (A) and step (B), between step (B) and step (E), or between step (F) and step (H).

[0133] In step (B), the resin composition layer is cured (for example, thermally cured) to form an insulating layer made of a cured product of the resin composition. The curing conditions for the resin composition layer are not particularly limited, and conditions that are usually adopted when forming an insulating layer for a printed wiring board may be used.

[0134] For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 140° C. to 250° C., more preferably 150° C. to 240° C., and even more preferably 180° C. to 230° C. The curing time is preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and even more preferably 15 minutes to 120 minutes.

[0135] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50° C. to 140° C., preferably 60° C. to 135° C., more preferably 70° C. to 130° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0136] <Process (C)> The method for producing a printed wiring board of the present invention may include, as an optional step, (C) a step of drilling holes in an insulating layer. This step allows holes such as via holes and through holes to be formed in the insulating layer. Step (C) may be performed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0137] <Process (D)> The method for producing a printed wiring board of the present invention may include, as an optional step, (D) a step of swelling the surface of the insulating layer. The swelling liquid used in the swelling treatment is preferably an alkaline solution containing an organic solvent. The organic solvent is not particularly limited, but examples thereof include glycol ethers such as diethylene glycol monobutyl ether and ethylene glycol. The alkaline solution is not particularly limited, but examples thereof include an aqueous solution of an alkali metal hydroxide, and is preferably an aqueous solution containing sodium hydroxide or potassium hydroxide. Examples of commercially available swelling liquids include "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan. The swelling treatment using a swelling liquid is not particularly limited, but can be performed by, for example, immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. In order to suppress swelling of the resin in the insulating layer to an appropriate level, the swelling treatment with the swelling liquid is preferably performed by immersing the insulating layer in the swelling liquid at 40° C. to 80° C. for 5 to 15 minutes.

[0138] <Steps (E) and (F)> The method for producing a printed wiring board of the present invention includes the step of (E) immersing the surface of the insulating layer in an aqueous liquid and then contacting the surface of the insulating layer with one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas.

[0139] In the first embodiment of the present invention, the aqueous liquid used in step (E) is an oxidizer solution. The oxidizer contained in the oxidizer solution is not particularly limited, but may be, for example, an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. A commercially available product may be used as the oxidizer solution. Examples of commercially available oxidizer solutions include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0140] The oxidizing agent solution in step (F) is T F (° C.), the temperature T of the oxidant solution used in step (E) in the first embodiment E1 (° C.) is preferably T F -70(℃) or higher, more preferably T F -60(℃) or higher, more preferably T F -40(℃) or more, T F -30(℃) or higher or T F The temperature of the oxidizer solution is -20°C or higher. E1 The upper limit of (°C) is preferably T F +20(℃) or less, more preferably T F +15(℃) or less, more preferably T F +10(℃) or less.

[0141] In the second embodiment of the present invention, the aqueous liquid used in step (E) is an aqueous liquid (excluding the swelling liquid) whose temperature difference with the oxidizing agent solution used in step (F) is 20° C. or less. The aqueous liquid may contain any solute as long as the effect of the present invention is exerted, but is preferably water. As the water, various types of water can be used depending on the purpose. As the water, for example, tap water or industrial water may be used, or pure water (electrical resistivity: 0.1 MΩ·cm or more and less than 1.5 MΩ·cm) or ultrapure water (electrical resistivity: 1.5 MΩ·cm or more) such as RO water, deionized water, and distilled water may be used. From the viewpoint of significantly obtaining the desired effect of the present invention, the aqueous liquid is preferably pure water.

[0142] The oxidizing agent solution in step (F) is T F (° C.), the temperature T of the aqueous liquid used in step (E) in the second embodiment E2 (℃) is T F -20(℃) or higher. The temperature of the aqueous liquid T E2 (° C.) is preferably T F -15(℃) or higher, more preferably TF -10 (℃) or higher. The temperature of the aqueous liquid T E2 (℃) upper limit is T F +20(℃) or less, preferably T F +15(℃) or less, more preferably T F +10(℃) or less.

[0143] In step (E), the time for immersing the surface of the insulating layer in the aqueous liquid is t E In step (F), the time for treating the surface of the insulating layer with the oxidizing agent solution is t F Then, t E and t F t is 0.02≦t E / (t E +t F It is preferable that the surface of the insulating layer satisfies the relational expression: 0.25≦0.25. When the surface of the insulating layer satisfies the relational expression, the occurrence of uneven roughening can be suppressed.

[0144] In step (E), the gas brought into contact with the surface of the insulating layer is one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas. From the viewpoint of significantly obtaining the desired effects of the present invention, the gas is preferably air.

[0145] In step (E), the time for contacting the insulating layer surface with the gas may be, for example, 5 seconds or more. From the viewpoint of significantly obtaining the desired effect of the present invention, the time for contacting the insulating layer surface with the gas is preferably 7 seconds or more, more preferably 10 seconds or more, and even more preferably 15 seconds or more. The upper limit of the time for contacting the insulating layer surface with the gas is preferably 120 seconds or less, more preferably 100 seconds or less, and even more preferably 60 seconds or less, from the viewpoint of not excessively cooling the surface of the substrate and suppressing the generation of minute bubbles caused by temperature differences.

[0146] The method for producing a printed wiring board of the present invention includes, after step (E), a step (F) of roughening the surface of the insulating layer with an oxidizing agent solution. The oxidizing agent contained in the oxidizing agent solution may be the same as the oxidizing agent that may be contained in the oxidizing agent solution used in step (E) in the first embodiment. The oxidizing agent solution used in step (F) may be the above-mentioned commercially available product. The temperature T of the oxidizing agent solution used in step (F) F (°C) is preferably 60°C or higher, more preferably 65°C or higher, even more preferably 70°C or higher, and is preferably 100°C or lower, more preferably 95°C or lower, even more preferably 90°C or lower.

[0147] In the first embodiment of the present invention, the oxidant solution used in step (F) may be the same as the oxidant solution used in step (E). For example, step (F) may be performed by immersing the surface of the insulating layer in the oxidant solution in step (E), taking out the insulating layer and contacting it with gas, and then immersing it again in the oxidant solution used in step (E).

[0148] In step (F), the time t F The time is not particularly limited as long as the surface of the insulating layer is sufficiently roughened, but is, for example, 5 minutes or more, preferably 10 minutes or more, and more preferably 15 minutes or more. F The upper limit is preferably 40 minutes or less, more preferably 30 minutes or less, and further preferably 25 minutes or less.

[0149] In the method for producing a printed wiring board of the present invention, when the method includes the step (C), smears that may occur in the step (C) can also be removed (desmeared) by carrying out the steps (E) and (F).

[0150] <Process (G)> The method for producing a printed wiring board of the present invention may include, as an optional step, (G) a step of neutralizing the surface of the insulating layer. The neutralizing liquid used in the neutralization is preferably an acidic aqueous solution. The neutralizing liquid used in the neutralization may be a commercially available product. An example of a commercially available neutralizing liquid is "Reduction Solution Securigant P" manufactured by Atotech Japan. The neutralization treatment using a neutralizing liquid is not particularly limited, but can be performed by immersing the treated surface that has been roughened with an oxidizing agent in a neutralizing liquid at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method of immersing an object that has been roughened with an oxidizing agent in a neutralizing liquid at 40°C to 70°C for 5 to 20 minutes is preferred.

[0151] <Process (H)> The method for producing a printed wiring board of the present invention may include, as an optional step, (H) a step of forming a conductor layer on an insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy, and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0152] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0153] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0154] In one embodiment, the conductor layer may be formed by plating. From the viewpoint of facilitating the formation of fine wiring, it is preferable to form the conductor layer by a semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0155] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0156] <Other matters related to printed wiring boards> In the method for producing a printed wiring board of the present invention, the above-mentioned steps may be repeated. For example, steps (A) to (H) may be repeated to produce a printed wiring board having a multilayer structure (multilayer printed wiring board) in which insulating layers and conductor layers are alternately provided.

[0157] [Printed wiring board] According to the above-mentioned manufacturing method, a printed wiring board including an inner layer substrate and an insulating layer formed on the inner layer substrate can be manufactured. In addition, when the manufacturing method of the printed wiring board includes a step (H) of forming a conductor layer on the insulating layer, the manufactured printed wiring board includes a conductor layer on the insulating layer.

[0158] [Semiconductor Devices] The above-mentioned printed wiring board can be used, for example, in the manufacture of a semiconductor device. A semiconductor device generally includes a printed wiring board and a semiconductor chip mounted on the printed wiring board. The printed wiring board manufactured by the above-mentioned manufacturing method can realize finer and higher density conductor layers as circuit wiring, and therefore can realize smaller size and higher functionality of electronic devices equipped with the semiconductor device.

[0159] Examples of the semiconductor device include various semiconductor devices used in electric appliances (eg, computers, mobile phones, digital cameras, televisions, etc.) and vehicles (eg, motorcycles, automobiles, trains, ships, aircraft, etc.).

[0160] A semiconductor device can be manufactured by mounting a semiconductor chip on a conductive portion of a printed wiring board. A "conductive portion" is a portion of a printed wiring board that transmits an electric signal, and the conductive portion may be either on the surface or embedded. An electric circuit element made of a semiconductor material may be used as the semiconductor chip.

[0161] The mounting method of the semiconductor chip is not particularly limited as long as the semiconductor chip functions effectively. For example, a wire bonding mounting method, a flip chip mounting method, a bumpless buildup layer (BBUL) mounting method, an anisotropic conductive film (ACF) mounting method, a non-conductive film (NCF) mounting method, etc. can be adopted. Here, the "bumpless buildup layer (BBUL) mounting method" refers to "a mounting method in which a semiconductor chip is directly embedded in a recess in a printed wiring board and the semiconductor chip is connected to the wiring on the printed wiring board." EXAMPLES

[0162] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature conditions are room temperature (23°C), and unless otherwise specified, the pressure conditions are atmospheric pressure (1 atm).

[0163] <Preparation Example 1: Preparation of Resin Composition 1> Tetramethylbisphenol type epoxy resin (Mitsubishi Chemical Corporation "YX4000H", epoxy group equivalent 194g / eq.) 8 parts, biphenyl aralkyl type epoxy resin (Nippon Kayaku Co., Ltd. "NC3000L", epoxy group equivalent approx. 271g / eq.) 10 parts, naphthalene type epoxy resin (DIC Corporation "HP6000L", epoxy group equivalent approx. 213g / eq.) 2 parts, bifunctional epoxy resin (Nippon Steel Chemical & Material Co., Ltd. "ZX1658GS", epoxy group equivalent approx. 133g / eq.) 2 parts, phenol-based hardener having triazine skeleton and cresol novolac structure (DIC Corporation "LA-3018-50P", phenol equivalent approx. 151g / eq., 2-methoxypropanol solution with solid content of 50%) 3 parts Resin composition 1 was prepared by adding 20 parts of an active ester resin (DIC Corporation's "HPC-8151-62T", active ester group equivalent weight approximately 238 g / eq., toluene solution with a solid content of 62%), 2 parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YL7800BH40", MEK and cyclohexane solution with a solid content of 40%), and 70 parts of an inorganic filler (Admatechs Corporation's "SO-C2", surface treatment amount: 0.6% by mass of amino silane coupling agent relative to 100% by mass of inorganic filler) that had been surface-treated with an amino silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM573", N-phenyl-3-aminopropyltrimethoxysilane), and 1 part of an MEK solution with a solid content of 5% of a curing accelerator (4-dimethylaminopyridine).

[0164] <Preparation Example 2: Preparation of Resin Composition 2> Resin composition 2 was prepared in the same manner as resin composition 1, except that the amount of active ester resin (DIC Corporation's "HPC-8151-62T") used was changed from 20 parts to 15 parts, and the amount of inorganic filler (Admatechs Corporation's "SO-C2") used was changed from 70 parts to 63 parts.

[0165] <Preparation Example 3: Preparation of Resin Composition 3> Resin composition 3 was prepared in the same manner as resin composition 1, except that the amount of active ester resin (DIC Corporation's "HPC-8151-62T") used was changed from 20 parts to 55 parts, and the amount of inorganic filler (Admatechs Corporation's "SO-C2") used was changed from 70 parts to 110 parts.

[0166] <Example 1> (1) Manufacturing of resin sheets The resin composition 1 prepared in Preparation Example 1 above was uniformly applied onto a PET film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) using a die coater so that the thickness after drying would be 18 μm. Thereafter, the film was dried in an oven to produce a resin sheet A having a layer structure of a resin composition layer / PET film.

[0167] A PET film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was laminated on the resin composition layer of resin sheet A using a roll laminator ("VA770" manufactured by Taisei Laminator Co., Ltd.) to produce resin sheet B having a layer structure of PET film / resin composition layer / PET film.

[0168] (2) Manufacturing of evaluation circuit boards The PET film on one side was peeled off from the obtained resin sheet B to expose the resin composition layer. In addition, a copper-clad laminate (Panasonic Electric Works "R1515A", copper layer thickness 18 μm, substrate thickness 0.8 mm) was prepared as a substrate. Using a batch-type vacuum pressure laminator (Nikko Materials Co., Ltd. two-stage build-up laminator "CVP700"), the resin sheet B was laminated on both sides of the copper-clad laminate so that the resin composition layer was in contact with the copper-clad laminate, and a substrate C having a layer structure of PET film / resin composition layer / copper-clad laminate / resin composition layer / PET film was produced. The lamination was performed by reducing the pressure for 30 seconds to 5 hPa or less, and pressing at a temperature of 100 ° C and a pressure of 0.7 MPa for 30 seconds. Next, a heat press was performed at a temperature of 100 ° C and a pressure of 0.55 MPa for 60 seconds.

[0169] Substrate C was placed in an oven at 180°C and heated for 30 minutes to thermally cure the resin composition layer, and the PET films on both sides were peeled off to form an insulating layer, thereby producing substrate D having a layer structure of insulating layer / copper-clad laminate / insulating layer.

[0170] (2-3) Wet roughening treatment The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), it was immersed in an oxidizing agent solution of the same conditions for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0171] <Example 2> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0172] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 4 minutes. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), it was immersed in an oxidizing agent solution of the same conditions for 16 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0173] <Example 3> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0174] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 30 seconds. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out, and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), it was immersed in an oxidizing agent solution of the same conditions for 19 minutes and 30 seconds, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0175] <Example 4> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0176] The insulating layer of the substrate D after the swelling treatment was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of about 6% and sodium hydroxide concentration of about 4%) at 25°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of about 6% and sodium hydroxide concentration of about 4%) at 80°C for 19 minutes, and rinsed by shower and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in a neutralizing solution (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of sulfuric acid) at 40°C for 5 minutes, rinsed by shower and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to prepare a roughened substrate E.

[0177] <Example 5> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0178] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 55°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out, and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), the substrate was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0179] <Example 6> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0180] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 65°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was taken out, and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), the substrate was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0181] <Example 7> A roughened substrate E was obtained in the same manner as in Example 1, except that resin composition 2 was used instead of resin composition 1.

[0182] <Example 8> A roughened substrate E was obtained in the same manner as in Example 1, except that resin composition 3 was used instead of resin composition 1.

[0183] <Example 9> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0184] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 90°C for 1 minute. After the insulating layer of the substrate D was immersed in the oxidizing agent solution, the substrate D was taken out, and within 30 seconds (specifically, 15 seconds after the substrate D was taken out), the substrate was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0185] <Example 10> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0186] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 90°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was removed, and 5 seconds after removing the substrate D, the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0187] <Example 11> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0188] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 90°C for 1 minute. After immersing the insulating layer of the substrate D in the oxidizing agent solution, the substrate D was removed, and 100 seconds after removing the substrate D, the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0189] <Example 12> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0190] The insulating layer of the substrate D was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in pure water at 80°C for 5 minutes. After immersing the insulating layer of the substrate D in pure water, the substrate D was removed, and within 30 seconds (specifically, 15 seconds after the substrate D was removed), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of approximately 6% and sodium hydroxide concentration of approximately 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0191] <Example 13> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0192] The insulating layer of the substrate D was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in pure water at 65°C for 5 minutes. After immersing the insulating layer of the substrate D in pure water, the substrate D was removed, and within 30 seconds (specifically, 15 seconds after the substrate D was removed), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of approximately 6% and sodium hydroxide concentration of approximately 4%) at 80°C for 20 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0193] <Example 14> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0194] The insulating layer of the substrate D was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in pure water at 90°C for 5 minutes. After immersing the insulating layer of the substrate D in pure water, the substrate D was removed, and within 30 seconds (specifically, 15 seconds after the substrate D was removed), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of approximately 6% and sodium hydroxide concentration of approximately 4%) at 80°C for 20 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0195] <Example 15> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0196] The insulating layer of the substrate D was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an aqueous solution of sodium carbonate with a concentration of about 5% by mass at 80°C for 5 minutes. After immersing the insulating layer of the substrate D in the aqueous solution of sodium carbonate, the substrate D was removed, and within 30 seconds (specifically, 15 seconds after the substrate D was removed), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate with a concentration of about 6% and sodium hydroxide with a concentration of about 4%) at 80°C for 20 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0197] <Comparative Example 1> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0198] The insulating layer of the substrate D was immersed in a swelling solution (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate at about 6% and sodium hydroxide at about 4%) at 80°C for 20 minutes, and rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in a neutralizing solution (Atotech Japan's "Reduction Solution Securigant P", an aqueous solution of sulfuric acid) at 40°C for 5 minutes, and rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce a roughened substrate E.

[0199] <Comparative Example 2> A roughened substrate E was obtained in the same manner as in Example 1, except that the wet roughening treatment was carried out as follows.

[0200] The insulating layer of the substrate D was immersed in a swelling liquid (Atotech Japan's "Swelling Dip Securigant P", an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of the substrate D was immersed in pure water at 55°C for 5 minutes. After immersing the insulating layer of the substrate D in pure water, the substrate D was removed, and within 30 seconds (specifically, 15 seconds after the substrate D was removed), it was immersed in an oxidizing agent solution (Atotech Japan's "Concentrate Compact CP", an aqueous solution of potassium permanganate concentration of approximately 6% and sodium hydroxide concentration of approximately 4%) at 80°C for 19 minutes, and then rinsed by showering and immersion in pure water at room temperature. Next, the insulating layer of Substrate D was immersed in a neutralizing solution (Reduction Solution Securigant P, a sulfuric acid aqueous solution manufactured by Atotech Japan) at 40°C for 5 minutes, rinsed by showering and immersion in pure water at room temperature, and then dried at 80°C for 15 minutes to produce roughened Substrate E.

[0201] <Evaluation of uneven roughening> Ten samples of 3 cm x 3 cm size of the roughened substrate E produced in each Example and Comparative Example were prepared, and ten samples of 2000 μm x 2000 μm in field of view were randomly selected from these, and the insulating layer surface after wet roughening was observed at a magnification of 25 times using a digital microscope (Keyence Corporation's "VHX-7000"). After that, the average number of spots per field of view was calculated using six samples, excluding the two samples with the most and two samples with the least number of spots. In addition, the unevenness of roughening was evaluated according to the following criteria. ○: The number of spots per field of view is less than 20. Δ: The number of spots per visual field is 20 or more and less than 40. ×: The number of spots per field of view is 40 or more.

[0202] <Evaluation of surface roughness> For the roughened substrate E produced in each Example and Comparative Example, a non-contact surface roughness meter (WYKO GT-3X manufactured by Bruker) was used to measure the surface area of ​​the insulating layer after the wet roughening treatment, with a green light source, VSI mode, and a 50x lens, with a measurement range of 126 μm × 94 μm, to determine the arithmetic mean roughness Ra. The arithmetic mean roughness Ra was measured by calculating the average value of 10 points for each. The surface roughness was evaluated according to the following criteria. ◯: Ra is greater than 50 nm and equal to or less than 200 nm. ×: Ra is 50 nm or less or more than 200 nm.

[0203] The evaluation results of each of the examples and comparative examples are summarized in Tables 1 to 3 below.

[0204] [Table 1]

[0205] [Table 2]

[0206] [Table 3]

[0207] [Consider] As shown in Tables 1 to 3, by carrying out a step of immersing the insulating layer surface in an aqueous liquid (an oxidant solution, or an aqueous liquid whose temperature difference with the oxidant solution used in the roughening treatment is 20°C or less) and further contacting it with gas prior to the step of roughening the insulating layer surface with an oxidant solution, it is possible to suppress uneven roughening that occurs when the insulating layer surface is roughened with an oxidant solution.

Claims

1. (E) a step of immersing the surface of the insulating layer in the aqueous liquid and then contacting the surface of the insulating layer with one or more gases selected from the group consisting of air, a rare gas, nitrogen gas, and carbon dioxide gas; and (F) a step of roughening the surface of the insulating layer with an oxidizing agent solution, in this order; A method for producing a printed wiring board, wherein the aqueous liquid used in the step (E) is the following (1) or (2): (1) Oxidizing agent solution (2) An aqueous liquid (excluding the swelling liquid) whose temperature difference with the oxidizing agent solution used in step (F) is 20° C. or less.

2. The method for producing a printed wiring board according to claim 1 , wherein the gas used in step (E) is air.

3. 3. The method for producing a printed wiring board according to claim 1, wherein in the step (E), the time for which the surface of the insulating layer is contacted with the gas is from 5 seconds to 120 seconds.

4. The method for producing a printed wiring board according to claim 3, wherein in the step (E), the time for which the surface of the insulating layer is contacted with the gas is from 10 seconds to 60 seconds.

5. In step (E), the time for immersing the surface of the insulating layer in the aqueous liquid is t E In the step (F), the time for treating the surface of the insulating layer with the oxidizing agent solution is t F When t E and t F but, 0.02≦t E / (t E +t F )≦0.25 The method for producing a printed wiring board according to claim 1 , which satisfies the following relational expression:

6. 2. The method for producing a printed wiring board according to claim 1, wherein the aqueous liquid used in step (E) is pure water.

7. The method for producing a printed wiring board according to claim 1 , further comprising the step (C) of drilling holes in the insulating layer prior to the step (E).

8. The method for producing a printed wiring board according to claim 1 , further comprising, after step (F), a step (H) of forming a conductor layer on the insulating layer.

9. Before step (E), (A) forming a resin composition layer containing a resin composition on an inner layer substrate; and (B) curing the resin composition layer to form an insulating layer, in this order.

10. The method for producing a printed wiring board according to claim 9 , wherein the resin composition contained in the resin composition layer comprises (a) an epoxy resin and (b) an active ester-based curing agent.

11. 11. The method for producing a printed wiring board according to claim 10, wherein when the number of epoxy groups in the epoxy resin (a) is taken as 1, the number of active ester groups in the active ester curing agent (b) is 0.3 or more and 2.0 or less.

Citation Information

Patent Citations

  • Method for manufacturing printed wiring board

    JP2021163825A